Strategi Edukasi Pola Asuh untuk Optimalisasi Tumbuh Kembang Balita di Desa Bresela - Sumadewi, Komang Trisna; Yupardhi, Toddy Hendrawan; Suryadiningrat, Gede Wahyu (Poltekkes Kemenkes Denpasar, 2024)
The growth and development of children under five in Indonesia still faces significant challenges, mainly due to inadequate parenting and a lack of parental knowledge about the importance of early detection of child growth and development disorders. The high prevalence of stunting and developmental delays is an urgent problem to be overcome. Based on the interviews, priority problems were obtained, including lack of knowledge of parenting, monitoring of children's growth and development, and the skills of the family of toddlers related to the growth and development of children. The service team offers solutions through training for parents in Bresela Village, in order to improve understanding and skills in monitoring children's growth and development using KMS and KPSP as a guide. The implementation method includes pretests, providing educational materials, monitoring demonstrations, and posttests to assess knowledge improvement. The results of the activity showed an increase in parents' knowledge by 50% about parenting and 40% about the growth and development of children after training. In addition, there is an increase in family skills in monitoring growth and development independently. In conclusion, this program has succeeded in increasing the awareness and ability of parents to optimize children's growth and development, but it needs to be continued with continuous assistance and socialization to overcome existing problems. Keywords: Toddler Growth, Toddler Development, Parenting Style